Political discourse and national identity in Scotland - Leith, Murray Stewart; Soule, Daniel P. J. (Edinburgh University Press, 2011)
Uses manifesto analysis to measure political nationalism in Scotland Murray Leith and Daniel P.J. Soule explore the importance of groups, concepts and events such as the SNP and devolution, unionism, the political elite, political and public discourse, inclusion and exclusion, enforced nationalism, and birth, race and citizenship to nationalist feeling in Scotland. The authors set the Modernist view of Scottish nationalism against the work of Gellner, Anderson and Billig to create their own 'mixed method' of evaluating nationalism. Key Features Presents a detailed consideration of the language used within the political and nationalist arena in Scotland Compares a variety of attitudes and opinions held within Scotland from the political elite to the masses Introduces a new method for measuring political nationalism using manifesto analysis